Familiarity, Current Use, and Interest in Universal Design for Learning Among Online University Instructors - Carl D Westine (Athabasca University Press, 2019)
This study investigated online faculty familiarity, course design use, and professional development interest regarding universal design for learning (UDL) guidelines. The researchers surveyed all 2017 to 2018 online faculty at a large university in the southeastern United States. Findings included 71.6% of faculty reporting familiarity with at least one UDL guideline, with most respondents indicating familiarity with guidelines relating to perception, expression, and communication. Faculty reported the highest implementation of UDL guidelines was for those suggesting options for comprehension as well as expression and communication; the lowest implementation was for those suggesting options for physical action as well as language and support. Survey results also indicated high to moderate interest in learning more about all UDL guidelines, with emphasis on comprehension, persistence, and expression. This study suggests that faculty members desire UDL training and offers possibilities for planning and implementing such professional development in areas targeted to best meet the needs of online faculty.